2008
DOI: 10.1021/bi800991e
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Antimicrobial C3a Analogues with Enhanced Effects against Staphylococci Using an Integrated Structure and Function-Based Approach

Abstract: The anaphylatoxin C3a and its inactivated derivative C3adesArg, generated during complement activation, exert direct antimicrobial effects, mediated via its C-terminal region [Nordahl et al. (2004) Proc. Natl. Acad. Sci. U.S.A. 101, 16879-16884]. During evolution, this region of C3a displays subtle changes in net charge, while preserving a moderate but variable amphipathicity [Pasupuleti et al. (2007) J. Biol. Chem. 282, 2520-2528]. In this study, we mimic these evolutionary changes, employing a design approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 66 publications
3
60
0
Order By: Relevance
“…Other studies previously identified charge as a critical parameter for activity of helical AMPs (48); decreasing the net charge below ϩ3 reduces potency, while increasing the net charge gradually increases activity (49,50). In this context, it is interesting that positive charge selection appears to characterize the evolution of ␤-defensins and that hBD3, the human defensin with the highest positive net charge (ϩ10), also has the highest activity against S. aureus (51).…”
Section: Discussionmentioning
confidence: 96%
“…Other studies previously identified charge as a critical parameter for activity of helical AMPs (48); decreasing the net charge below ϩ3 reduces potency, while increasing the net charge gradually increases activity (49,50). In this context, it is interesting that positive charge selection appears to characterize the evolution of ␤-defensins and that hBD3, the human defensin with the highest positive net charge (ϩ10), also has the highest activity against S. aureus (51).…”
Section: Discussionmentioning
confidence: 96%
“…In most cases, trials are aimed at topical indications where direct microbicidal effects are utilized. Considering this property of AMPs, various strategies have been employed in order to optimize the therapeutic index, including the use of combinational library approaches (1), stereoisomers composed of Damino acids (40) or cyclic D,L-␣-peptides (8), and quantitative structure-activity relationship (QSAR) and high-throughputbased screening assays (9,15,18,35,44). Furthermore, a novel approach for boosting AMPs through end-tagging with hydrophobic oligopeptide stretches has recently been demonstrated (23,32,33,41).…”
Section: Discussionmentioning
confidence: 99%
“…Minimal Inhibitory Concentration Assay-MIC assay was carried out by a microtiter broth dilution method as described previously (11,29) with slight modifications. For preparation of refined media, 100 ml of Luria Bertani broth was prepared in 10 mM Tris, pH 7.4, and applied to a column packed with 40 ml of DEAE Sephacel (9013-34-7; Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%